Possible induction of systemic resistance to Lasiodiplodia theobromae in avocado (Persea americana Mill.) under semi-controlled conditions at La Molina - Jimenez-Ariza, Nery Veronica (2023)
The production and export of avocado fruits, cultivar Hass, has grown exponentially in recent years in Peru, however, a high incidence of symptoms such as regressive death, cankers on plant branches, and fruit rot have been observed affecting optimal crop production and fruit quality. These symptoms are mainly generated by Lasiodiplodia theobromae fungus, whose control is limited to a few active ingredients that tend to generate pathogen resistance. The present investigation had as objective to evaluate the inducing effect of resistance in the control of Lasiodiplodia theobromae in avocado (Persea americana) cultivar Hass of five bioproducts: ProtecSea, Barrera, Timorex Gold, T 22, Vacun Q Pro and water as a control treatment, with a total of 6 treatments with 4 replications, 3 avocado trees per replication.  One-year-old avocado trees cultivar Hass were used. Treatments were applied three times via drench at ten-day intervals. Five days after the last application L. theobromae was inoculated in the avocado trees cultivar ‘ Hass’ and 40 days after the inoculation, the parameters were evaluated: length of the disease lesion, percentage of dry matter of the roots and leaves, and length of the roots. It was observed that treatments, with the exception of treatment T1 (Control), reduced the length of the disease lesion infected by L. theobromae inside the stem. Treatment T6 (T.22) resulted in a higher percentage of root dry matter (46.52 %) compared to the control treatment (41.21 %). On the other hand, there were no significant differences in leaf dry matter content among treatments. Additionally, it was observed that treatment T2 (ProtecSea) reported a root length of 56.80 cm, followed by treatment T6 (T.22) with 54.90 cm. These results are important to continue with investigations into inducing systemic resistance in plants.